2010
DOI: 10.1002/ibd.21150
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 in experimental colitis

Abstract: The pathophysiology of inflammatory bowel disease (IBD) includes leukocyte infiltration, blood and lymphatic remodeling, weight loss and protein enteropathy. The roles of angiopoietin-2 (Ang-2) in initiating gut inflammation, leukocyte infiltration and angiogenesis are not well understood. Several important differences were seen in the development of experimental IBD in Ang-2-/- mice. Although weight change and disease activity differ only slightly in WT and Ang-2-/- + DSS treated mice, leukocyte infiltration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 59 publications
6
51
1
Order By: Relevance
“…These functional data add weight to the suggestion that Ang-2 is a key trigger of inflammatory lymphangiogenesis. A recent study (15) showed that lymphangiogenesis and inflammation are significantly reduced in an inflammatory bowel disease model using Ang-2 Ϫ/Ϫ mice, supporting the hypothesis that Ang-2 is one of the key regulators involved in inflammatory lymphangiogenesis. Previous studies have shown that inflammatory C: significant inhibition of lymphangiogenesis (P Ͻ 0.01, n ϭ 7) by L1-10.…”
Section: Discussionmentioning
confidence: 76%
“…These functional data add weight to the suggestion that Ang-2 is a key trigger of inflammatory lymphangiogenesis. A recent study (15) showed that lymphangiogenesis and inflammation are significantly reduced in an inflammatory bowel disease model using Ang-2 Ϫ/Ϫ mice, supporting the hypothesis that Ang-2 is one of the key regulators involved in inflammatory lymphangiogenesis. Previous studies have shown that inflammatory C: significant inhibition of lymphangiogenesis (P Ͻ 0.01, n ϭ 7) by L1-10.…”
Section: Discussionmentioning
confidence: 76%
“…Serum albumin was determined by densitometry and by the bromcresol purple method as reported (23,24). Densitometric analysis of PAGEseparated proteins were done using Molecular Imager (ChemiDoc Lab TM XRS, Bio-Rad) equipped with Image Lab TM software.…”
Section: Methodsmentioning
confidence: 99%
“…115,120 Although increased density of lymphatics is a characteristic of experimental and clinical IBD, lymphatic vessel dilation and edema formation in IBD could also be a consequence of impaired contractile function of the intestinal lymphatics. 121,122 In rat and guinea pig models of intestinal inflammation, indeed, the contractile capacity within isolated collecting mesenteric lymphatics is compromised, and this effect correlates with lymphatic dysfunction, lymphatic vessel dilation and mucosal inflammation. 88,103,123,124 Furthermore, these studies have shown cyclooxygenase (cyclooxygenase 1/2) or inducible nitric oxide synthase inhibitors improve lymphatic pumping in non-contracting lymphatics in experimental IBD, suggesting prostanoids and nitric oxide released during intestinal inflammation contribute to diminished lymphatic contractile activity.…”
Section: Roles Of Lymphatics In Inflammationmentioning
confidence: 99%